L-DOPA ELICITATION THROUGH CALCIUM ION MEDIATED CHANNEL IN CALLUS CULTURES OF MUCUNA PRURIENS - SUNDARESAN, UMA; PARAMESWARAN, GURUMOORTHI; MANIVANNAN, KAVITHA (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: The production of L-Dopa in callus cultures of Mucuna pruriens is influenced by substances that regulate calcium channels. Methods: M. pruriens seeds were gathered from the Western Ghats area in Tamil Nadu. L-Dopa was obtained by the Brain (1976) method, A. niger cultures were used for fungal elicitor preparation, and the assay of Ca2+ATPase was studied. Results: The use of fungal triggers resulted in increased L-Dopa levels on the 9th day but reduced levels on the 24th day of culture. When calcium channel modulators like verapamil and chlorpromazine were added, it decreased the growth of calli and L-Dopa production, suggesting the role played by calcium ion channels in L-Dopa synthesis. The calcium ionophore A23187 enhanced calli growth and L-Dopa production, increasing Ca2+ATPase activity. Particularly on the 12th d, Ca2+ATPase was notably active, while the presence of calcium ionophore boosted L-Dopa biosynthesis. Conclusion: The use of fungal elicitors in in vitro cultures of Mucuna pruriens is recommended as a potential method to increase the production of secondary metabolites.